2019
DOI: 10.2174/1570178615666181106125853
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Synthesis of Chiral Oxime Ethers

Abstract: An efficient and rapid synthesis of a new class of chiral oxime ethers has been achieved via two-step reaction in which the first step is the reaction of oximes 1a-f with ethyl bromoacetate in the presence of sodium hydride to give oxime ethers 2a-f which are subsequently, in the second step, reacted with different commercially available chiral amines under microwave irradiation conditions to give compounds 3a-l in good to excellent yields. Through this method, we have observed a decrease in reaction time and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Microwave-assisted synthesis has a large impact on synthetic organic chemistry. Microwave-enhanced organic synthesis typically reduces reaction times and sometimes improves product yields [ 14 ]. In order to determine the influence of reaction conditions on the product isomer ratio, several microwave-assisted reactions were conducted ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microwave-assisted synthesis has a large impact on synthetic organic chemistry. Microwave-enhanced organic synthesis typically reduces reaction times and sometimes improves product yields [ 14 ]. In order to determine the influence of reaction conditions on the product isomer ratio, several microwave-assisted reactions were conducted ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The aim was to investigate the stereoselectivity of reactions and the influence of the reaction conditions on ( E ) and ( Z ) ratios. For this purpose, three different methods were used and compared: solvent [ 10 ], mechanochemical [ 12 , 13 ] and microwave [ 14 , 15 ] synthesis. Recent studies reported mechanochemical and microwave syntheses of oxime heterocyclic compounds and defined the stereoselectivity of those reactions [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%